Onasemnogene Abeparvovec Administration via Peripherally Inserted Central Catheter: A Case Report - Inmaculada Pitarch Castellano; Eduardo López Briz; Eugenia Ibáñez Albert; Cristina Aguado Codina; Teresa Sevilla; José L. Poveda Andrés (MDPI AG, 2024)
Onasemnogene abeparvovec (OA) is the approved intravenous gene therapy for the treatment of spinal muscular atrophy (SMA). A functional copy of the human SMN1 gene was inserted into the target motor neuron cells via a viral vector, AAV9. In clinical trials, OA was infused through a peripheral venous catheter, and no data are available on central catheter use. Recently, we had a case where OA was administered directly into the right atrium via a peripherally inserted central catheter (PICC) instead of a peripheral line, as recommended. The patient was a female child aged 4 months, diagnosed as SMA type I. For practical reasons, a dose of OA according to the weight of the patient (1.1 × 1014 vectorial genomes/kg) was administered via PICC in 1 h, as the product information recommends. The drug was well tolerated, with no hypersensitivity reactions or initial elevation of transaminases or other adverse effects. To our knowledge, this is the first case reported where OA was administered via a central line. This type of administration is not contraindicated, but it is not specifically contemplated or recommended. It is unknown whether central line administration could have any implications for transduction efficiency and immunogenicity. Future studies should clarify these aspects, as each gene therapy has a specific optimal dose recorded that depends on the site and route of administration of the drug, the AAV variant and the transgene.